A solid amine low-temperature carbon capture material for low-temperature CO 2 Application in adsorption
By regulating the amine load ratio and metal molar ratio, the prepared 60PEI-Mg0.55Al-CO3-AMOST material has excellent CO2 adsorption capacity and recycling under low temperature conditions, solving the problem of performance attenuation caused by amine leaching in the prior art in the prior art , significantly improves the performance and stability of the low-temperature CO2 capture technology of solid amine.
Patent Information
- Application Number
- CN202311046110.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-08-18
AI Technical Summary
The existing solid amine low-temperature CO2 capture materials have attenuated performance due to amine leaching during multiple adsorption-desorption cycles, and the interaction force with traditional silicon-based carriers is weak, resulting in poor CO2 adsorption performance, limiting the scale of the technology. .
Hydral talc-like materials treated with polyethyleneimine were prepared by regulating the amine loading ratio and the molar ratio of divalent/trivalent metals to prepare 60PEI-Mg0.55Al-CO3-AMOST solid amine with excellent CO2 adsorption capacity and recycling ability. The low-temperature carbon capture material is modified using a one-step impregnation method, and the pore structure of the material is lifted by organic solvent treatment.
It has achieved excellent CO2 adsorption capacity, recycling and oxidation resistance under low temperature conditions, with a performance loss of only 6.7%, which significantly improved the performance and stability of the low-temperature CO2 capture technology of solid amine.
Smart Images

Figure CN116832790B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to application of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption. Background Art
[0002] Global warming is a global climate problem that needs to be solved urgently. Among them, carbon dioxide (CO2), as the main greenhouse gas, contributes up to 55% to the greenhouse effect. Most of CO2 comes from the combustion of fossil energy, so the capture of industrial source CO2 is considered an important solution to global climate change.
[0003] Solid amine materials have become the most promising low-temperature carbon capture technology due to their excellent CO2 adsorption capacity, low regeneration energy consumption and low corrosion to capture devices. However, the interaction between organic amine groups and traditional silicon-based carriers is relatively weak, resulting in the prepared solid amine adsorbents generally having poor CO2 adsorption performance. Qi et al. used organic amines to functionalize nano-silica to prepare a series of solid amine materials and tested their CO2 adsorption performance. They found that the materials were prone to significant performance degradation due to amine leaching during multiple adsorption-desorption cycles, which greatly increased the capture cost. Therefore, it is crucial to synthesize a porous material with a large pore volume / diameter that can bind to organic amine groups through strong forces for the large-scale application of solid amine low-temperature carbon capture technology.
[0004] In general, although solid amine low-temperature CO2 capture technology has reached a high level of technical maturity, it still has a long way to go before large-scale development and application. There is still a lot of room for improvement in the research and development of solid amine materials. The manufacture of cheap adsorbents with high CO2 adsorption capacity, fast adsorption kinetics and good adsorption-desorption stability is crucial for the large-scale deployment of industrial decarbonization processes. Summary of the invention
[0005] The object of the present invention is to provide a solid amine low-temperature carbon capture material for use in low-temperature CO2 adsorption.
[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0007] A solid amine low-temperature carbon capture material is used in low-temperature CO2 adsorption, characterized in that the composition system of the material is a hydrotalcite-like material treated with polyethyleneimine PEI-organic solvent, and its chemical composition is yPEI-A xBC-AMOST, y is the mass fraction of PEI in the material, A and B are the divalent and trivalent metal elements that constitute the hydrotalcite-like lamellae, C is the anion between the layers, x is the molar ratio of the divalent and trivalent metal elements, y is 40-70wt%, x is 0.55-3, and AxB-C-AMOST is a hydrotalcite-like lamellae prepared by a water-soluble organic solvent treatment method. The preparation method of the solid amine low-temperature carbon capture material comprises the following steps: (1) mixing two or more precursor substances containing A and B respectively to form a precursor solution; (2) adding the precursor solution to an alkaline solution to obtain a mixed solution, controlling the pH value of the mixed solution, and aging the mixed solution; (3) filtering and washing the aged mixed solution in deionized water and an organic solvent in succession, comprising: repeatedly washing the mixed solution with deionized water under the condition of filtering until the pH value of the filtrate is 7, and then washing it with an organic solvent 1 to 2 times when the filtrate is almost dried, and drying it to obtain a precipitate; placing the obtained precipitate in a container containing an organic solvent, and fully stirring it at room temperature, and then filtering it again, repeatedly washing the filter cake with an organic solvent, and then vacuum drying to obtain a hydrotalcite-like material containing A and B; (4) using a one-step impregnation method to modify the obtained hydrotalcite-like material using polyethyleneimine, and obtaining the yPEI-A after vacuum drying. x BC-AMOST solid amine low temperature carbon capture material.
[0008] The application of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption is characterized in that the chemical composition of the hydrotalcite-like material is A x In BC, A is Mg 2+ 、Zn2+、Ni 2+ 、Co 2+ , Cu 2+ , Ca 2+ , Mn 2+ , Fe 2+ 、Zn 2+ At least one of the following, B is A1 3+ Cr 3+ 、Co 3+ , Fe 3+ , Ga 3+ At least one of the following, C is CO3 2- , NO3 - , SO4 2 -, C2O4 2- , Cl - At least one of them.
[0009] The application of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption is characterized in that y is 60wt%, A, B, and C are Mg 2+ 、Al 3+ 、CO32- , x is 0.55, chemical composition is 60PEI-Mg 0.55 Al-CO3-AMOST.
[0010] The application of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption is characterized in that the temperature range for CO2 capture is 25 to 85°C, and the captured CO2 concentration range is 0.04 to 100%.
[0011] The application of the solid amine low-temperature carbon capture material in low-temperature CO2 adsorption is characterized in that the pH value of the mixed solution in step (2) is controlled within the range of 8 to 12.
[0012] The preparation method is characterized in that the pH value of the mixed solution in step (2) is controlled within the range of 9.5 to 10.5, the aging temperature is 25 to 80° C., and the aging time is greater than 2 hours.
[0013] The application of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption is characterized in that the organic solvent in step (3) is specifically at least one of anhydrous methanol, anhydrous ethanol and acetone, the vacuum drying temperature is 25 to 120°C, and the vacuum degree is -0.1 to 0 MPa.
[0014] The application of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption is characterized in that the one-step impregnation process in step (4) is specifically as follows: adding a certain mass of polyethyleneimine to an organic solvent and stirring it fully at room temperature; weighing a certain mass of hydrotalcite-like material and placing it in the polyethyleneimine solution and continuing to stir vigorously at room temperature; using a rotary evaporator to remove the organic solvent in the mixed solution, and obtaining the yPEI-A after vacuum drying. x BC-AMOST solid amine low temperature carbon capture material.
[0015] The preparation method is characterized in that the stirring process in step (4) is carried out under air-tight conditions.
[0016] The preparation method is characterized in that the isolated air is nitrogen aeration, the rotation speed is 10-100 rpm, the temperature of the vacuum drying oven is 25-120° C., and the vacuum degree is -0.1-0 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The present invention prepares 60PEI-Mg with different A / B molar ratios x Adsorption-desorption cycle performance diagram of Al-CO3-AMOST solid amine carbon capture material.
[0018] Figure 2 60PEI-Mg prepared by the present invention 0.55 Al-CO3-AMOST solid amine carbon capture material and comparative sample 60PEI-Mg 0.55 Comparison of the antioxidant properties of Al-O-MMO solid amine carbon capture materials.
[0019] Figure 3 60PEI-Mg prepared by the present invention 0.55 Al-CO3-AMOST solid amine carbon capture material and comparative sample 60PEI-Mg 0.55 Comparison of saturated CO2 adsorption capacity of Al-CO3-Water solid amine carbon capture materials.
[0020] Figure 4 60PEI-Mg prepared by the present invention 0.55 Al-CO3-AMOST solid amine carbon capture material and comparative sample 60TEPA-Mg 0.55 Comparison of the adsorption-desorption cycle performance of Al-CO3-AMOST solid amine carbon capture materials.
[0021] Figure 5 60PEI-Mg prepared by the present invention 0.55 Comparison chart of saturated CO2 adsorption capacity of Al-CO3-AMOST solid amine carbon capture material and comparison samples 60PEI-MCM-41 traditional silicon-based solid amine carbon capture material and 60PEI-SBA-15 traditional silicon-based solid amine carbon capture material. DETAILED DESCRIPTION
[0022] The present invention provides an application of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption. The adsorbent has excellent CO2 adsorption capacity, recyclability and antioxidant properties under low-temperature conditions. The present invention uses polyethyleneimine to modify the mesoporous hydrotalcite-like material after organic solvent washing, and prepares a series of organic amine-hydrotalcite-like composite solid materials by adjusting the amine loading ratio and the molar ratio of divalent / trivalent metals, and tests its low-temperature CO2 adsorption performance and antioxidant properties. The adsorbent of the specific example is 60PEI-Mg 0.55 Take Al-CO3-AMOST as an example.
[0023] Example 1. yPEI-A with different PEI loadings (40-70 wt%) x BC-AMOST adsorbent
[0024] (1) 60PEI-Mg 0.55 Preparation method of Al-CO3-AMOST adsorbent (one-step impregnation method)
[0025] Dissolve 9.098g Mg(NO3)2·6H2O and 24.200g Al(NO3)3·9H2O in 100mL deionized water to obtain a stable, transparent mixed solution. Add the mixed solution dropwise to 100mL solution containing 5.299g Na2CO3 under room temperature and vigorous stirring. Use 4mol / L NaOH solution to keep the pH value of the mixed solution at about 10.0 during the addition. After the addition is completed, the resulting solution is aged for 12h at room temperature.
[0026] Under the condition of suction filtration, the aged solution is repeatedly washed with deionized water until the pH value of the filtrate is 7. When the filtrate is almost dried, it is washed with ethanol 1 to 2 times and dried to obtain a precipitate. The obtained precipitate is placed in a beaker containing 100 to 200 mL of ethanol, fully stirred for 2 hours at room temperature, and then filtered. The filter cake is repeatedly washed with ethanol. The obtained filter cake is placed in a vacuum drying oven at 60°C and dried for 12 hours, and then ground into a powder state to obtain Mg 0.55 Al-CO3-AMOST hydrotalcite.
[0027] 0.75 g of polyethyleneimine was placed in 30 ml of methanol solution and stirred for 0.5 h at room temperature under nitrogen atmosphere. 0.5 g of dry Mg 0.55 The Al-CO3-AMOST hydrotalcite powder was placed in the above polyethyleneimine solution and stirred vigorously for 3 hours at room temperature and nitrogen atmosphere. The obtained solution was placed in a 60°C water bath and the methanol solvent in the solution was removed using a rotary evaporator at -0.1 MPa. The final 60PEI-Mg was then dried in a 60°C vacuum oven overnight. 0.55 Al-CO3-AMOST adsorbent.
[0028] 40PEI-Mg 0.55 The preparation method of Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The difference in the preparation method of Al-CO3-AMOST material is that 0.34 g of polyethyleneimine is placed in 30 ml of methanol solution.
[0029] 50PEI-Mg 0.55 The preparation method of Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The difference in the preparation method of Al-CO3-AMOST material is that 0.5 g of polyethyleneimine is placed in 30 ml of methanol solution.
[0030] 70PEI-Mg 0.55 The preparation method of Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg in Example 1.0.55 The preparation method of Al-CO3-AMOST material is different in that 1.15 g of polyethyleneimine is placed in 30 ml of methanol solution.
[0031] (2) Test method for CO2 adsorption capacity of adsorbent
[0032] The CO2 adsorption performance test experiment was carried out in a Q50 TA Instruments Q500 thermogravimetric analyzer (TGA). The sample amount was about 10 mg. The adsorption was carried out at 75°C and 10% CO2 for 60 min. The CO2 adsorption amount of the material was calculated by the mass difference of the sample before and after adsorption. The CO2 adsorption performance test method was used to measure the CO2 adsorption performance of yPEI-A with different PEI loadings. x The CO2 adsorption capacity of BC-AMOST adsorbent. The test results (as shown in Table 1) show that the PEI loading amount has a significant effect on the CO2 adsorption capacity of yPEI-A x The CO2 adsorption performance of BC-AMOST adsorbent was greatly affected. Initially, the adsorption capacity of the material increased with the increase of PEI loading. The higher PEI loading provided more adsorption sites. When the PEI loading was 60%, the adsorption capacity of the adsorbent was the highest, reaching 3.32mmol g -1 When the PEI loading amount was further increased to 70wt%, excessive amine accumulation caused the pores of the material to be blocked, and the adsorption capacity of the adsorbent decreased.
[0033] Table 1 Effect of different PEI loading amounts on yPEI-A x Effect test of BC-AMOST adsorbent on CO2 adsorption (adsorption temperature: 75℃, CO2 concentration: 10%)
[0034] PEI loading (wt%) 40 50 60 70 <![CDATA[CO2 adsorption capacity (mmol g -1 )]]> 2.64 3.22 3.32 3.22
[0035] Example 2. yPEI-A with different Mg / Al molar ratios (0-3) x BC-AMOST adsorbent
[0036] (1) yPEI-A with different Mg / Al molar ratios (0-3) x Preparation method of BC-AMOST adsorbent
[0037] The preparation method of 60PEI-Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The preparation method of Al-CO3-AMOST material is different in that 37.513 g Al(NO3)3·9H2O is dissolved in 100 mL deionized water.
[0038] The preparation method of 60PEI-Mg1Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg1Al-CO3-AMOST in Example 1. 0.55 The preparation method of Al-CO3-AMOST material was different in that 12.82 g Mg(NO3)2·66H2O and 18.76 g Al(NO3)3·9H2O were dissolved in 100 mL deionized water.
[0039] The preparation method of 60PEI-Mg2Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The preparation method of Al-CO3-AMOST material was different in that 17.10 g Mg(NO3)2·66H2O and 12.50 g Al(NO3)3·9H2O were dissolved in 100 mL deionized water.
[0040] The preparation method of 60PEI-Mg3Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The preparation method of Al-CO3-AMOST material was different in that 19.23 g Mg(NO3)2·66H2O and 9.38 g Al(NO3)3·9H2O were dissolved in 100 mL deionized water.
[0041] (2) Adsorption-desorption cycle performance test of solid amine materials
[0042] The CO2 adsorption-desorption cycle performance of different samples was tested using a Q50 TA Instruments Q500 thermogravimetric analyzer (TGA). About 10 mg of the sample was weighed and adsorbed for 10 minutes at 75°C and 10% CO2 / N2, then heated to 120°C and desorbed in a high-purity N2 atmosphere for 15 minutes, which was one cycle, and so on.
[0043] The CO2 adsorption capacity test method in Example 1 and the above-mentioned adsorption-desorption cycle performance test method were used to measure the yPEI-A with different Mg / Al molar ratios (0-3). x The cyclic performance of BC-AMOST adsorbent. Adsorption capacity test results (Table 2) and cyclic performance test results ( Figure 1The results of the above data show that with the increase of Mg / Al molar ratio, the CO2 adsorption capacity and recycling performance of the adsorbent first increase and then decrease. The Al-CO3-AMOST material prepared when the Mg / Al molar ratio is 0 is not actually a stacked nanosheet structure similar to hydrotalcite. After loading with amine, the dispersion rate of its organic amine sites is low, resulting in low amine utilization, low adsorption capacity and recycling performance. When the Mg / Al molar ratio is 0.55, the higher Al content leads to the formation of Al(OH)3 impurities, which inhibits the further growth of LDH and forms a fragmented nanosheet structure with extremely small lateral size, exposing a large number of hydroxyl sites suitable for organic amine binding. The CO2 adsorption capacity is the highest, which is 3.32 mmol g -1 , and maintained the highest stability in 100 adsorption-desorption cycle tests; further increasing the Mg / Al molar ratio, the adsorption capacity and stability continued to decrease. When the Mg / Al molar ratio was 3, the adsorption amount was only 1.02 mmol g -1 When the Mg / Al molar ratio is 1, 2, and 3, the performance losses in 100 adsorption-desorption cycle tests reach 11.2%, 19.7%, and 50%, respectively.
[0044] Table 2 Effect of Mg / Al molar ratio (0-3) on yPEI-A x Effect test of BC-AMOST adsorbent on CO2 adsorption capacity (adsorption temperature: 75°C, CO2 concentration: 10%, adsorption time: 1h)
[0045]
[0046] Table 3 Effect of Mg / Al molar ratio (0-3) on yPEI-A x Effect of BC-AMOST adsorbent on CO2 absorption-desorption cycle performance
[0047]
[0048] Example 3. Effect of adsorption temperature on yPEI-A x Effect of adsorption performance of BC-AMOST adsorbent
[0049] In order to systematically explore the effect of adsorption temperature on the adsorption performance of the adsorbent, 60PEI-Mg 0.55 Al-CO3-AMOST adsorbent was used as the research object, and its CO2 adsorption capacity at different adsorption temperatures (70-85°C) was tested. The results are shown in Table 4. By comparison, it can be seen that 60PEI-Mg 0.55 The Al-CO3-AMOST adsorbent has the highest CO2 adsorption capacity at 75 °C, and the adsorption capacity reaches 3.32 mmol g after 2 h of adsorption in 10% CO2 atmosphere. -1 .
[0050] Table 4 Effect of adsorption temperature on 60PEI-Mg 0.55 Effect test of cyclic stability of Al-CO3-AMOST adsorbent (CO2 concentration of 10%, adsorption time of 1h)
[0051]
[0052]
[0053] Comparative Example 1. Mg after calcination of PEI modification 0.55 Al-O MMO adsorbent (calcination temperature is 200℃, 300℃, 400℃, 450℃)
[0054] (1) Mg after calcination by PEI modification 0.55 Preparation method of Al-O MMO adsorbent
[0055] 60PEI-Mg 0.55 The preparation method of Al-O MMO (200 ° C) adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The preparation method of Al-CO3-AMOST material is different in that the Mg 0.55 Al-CO3-AMOST hydrotalcite powder was calcined in a tube furnace at 200℃ in N2 atmosphere for 5h to obtain Mg 0.55 Al-O MMO, take 0.5 g of dry Mg 0.55 Al-O MMO powder was placed in polyethyleneimine solution.
[0056] 60PEI-Mg 0.55 The preparation method of Al-O MMO (300 ° C) adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The preparation method of Al-CO3-AMOST material is different in that the Mg 0.55 Al-CO3-AMOST hydrotalcite powder was placed in a tube furnace and calcined at 300℃ in N2 atmosphere for 5h to obtain Mg 0.55 Al-O MMO, take 0.5 g of dry Mg 0.55 Al-O MMO powder was placed in polyethyleneimine solution.
[0057] 60PEI-Mg 0.55 The preparation method of Al-O MMO (400 ° C) adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55The preparation method of Al-CO3-AMOST material is different in that the Mg 0.55 Al-CO3-AMOST hydrotalcite powder was calcined in a tube furnace at 400℃ in N2 atmosphere for 5h to obtain Mg 0.55 Al-O MMO, take 0.5 g of dry Mg 0.55 Al-O MMO powder was placed in polyethyleneimine solution.
[0058] 60PEI-Mg 0.55 The preparation method of Al-O MMO (450°C) adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The preparation method of Al-CO3-AMOST material is different in that the Mg 0.55 Al-CO3-AMOST hydrotalcite powder was placed in a tube furnace and calcined for 5 h at 450 °C in N2 atmosphere to obtain Mg 0.55 Al-O MMO, take 0.5 g of dry Mg 0.55 Al-O MMO powder was placed in polyethyleneimine solution.
[0059] (2) Antioxidant performance test of solid amine materials
[0060] About 10 mg of the material was oxidized at 120°C (CO2 desorption temperature) and 100% O2 for 1 hour. The CO2 adsorption capacity of the material before and after oxidation was tested using a Q50 TAInstruments Q500 thermogravimetric analyzer (TGA). The antioxidant properties of different materials were compared by comparing the changes in adsorption performance before and after oxidation treatment.
[0061] The above test method was used to test the sample 60PEI-Mg 0.55 Al-CO3-AMOST adsorbent and 60PEI-Mg prepared in Comparative Example 1 0.55 Al-O MMO (200℃) adsorbent, 60PEI-Mg 0.55 Al-O MMO (300℃) adsorbent, 60PEI-Mg 0.55 Al-O MMO (400℃) adsorbent and 60PEI-Mg 0.55 The antioxidant properties of Al-O MMO (450℃) adsorbents were tested and compared. The test results (as shown in Table 5) show that the 60PEI-Mg 0.55 After Al-CO3-AMOST was oxidized under 100% O2 and 120℃ for 1h, its CO2 adsorption performance did not decrease, indicating that it has excellent antioxidant capacity.0.55 Al-CO3-AMOST adsorbent, Mg 0.55 Comparative sample 60PEI-Mg prepared by calcining Al-CO3 LDH and then loading PEI 0.55 The oxidation resistance of Al-O MMO adsorbent is poor, and the performance shows a significant attenuation after oxidation treatment. The CO2 adsorption retention rate is less than 95%, and the antioxidant capacity decreases with the increase of LDH calcination temperature. This is because the abundant hydroxyl groups on the surface of LDH can form hydrogen bonds with organic amines to protect the amine groups from being oxidized by oxygen, while calcination treatment will cause dehydroxylation reaction on the surface of LDH, resulting in the exposure of organic amine sites, which greatly weakens the antioxidant capacity of the material.
[0062] Table 5 Effect of calcination treatment on the antioxidant properties of the adsorbent (oxidation temperature is 120°C, oxygen concentration is 100%, oxidation time is 1h; adsorption temperature is 75°C, CO2 concentration is 10%, adsorption time is 1h)
[0063]
[0064] Comparative Example 2. Mg modified by PEI without organic solvent treatment 0.55 Al-CO3-Water Adsorbent
[0065] 60PEI-Mg 0.55 The preparation method of Al-CO3-Water adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The preparation method of Al-CO3-AMOST material is different in that the aged solution is repeatedly washed with deionized water until the pH value of the filtrate is 7, and then the precipitate is directly dried. The obtained precipitate is placed in a vacuum drying oven at 60°C and dried for 12 hours, and then ground into powder to obtain Mg 0.55 Al-CO3-Water LDH.
[0066] The adsorption capacity of 60PEI-Mg prepared in Comparative Example 2 was determined by the adsorption capacity test method in Example 1. 0.55 The CO2 adsorption performance of Al-CO3-Water adsorbent. The test results (Table 6) show that: Mg 0.55 The CO2 adsorption capacity of Al-CO3-Water adsorbent after PEI modification was only 0.42 mmol g -1 Compared with the 60PEI-Mg prepared by the present invention 0.55 Al-CO3-AMOST adsorbent (3.32 mmol g -1), its adsorption performance decreased by 87.5%. This is because the organic solvent washing (AMOST) treatment causes the interlayer water of LDH to be replaced by organic solvent, which can effectively reduce the lateral size of LDH nanosheets, causing them to peel off to form a typical slit-like mesoporous structure with a high pore volume / capacity, which is conducive to the loading and dispersion of PEI.
[0067] Table 6 Effect of AMOST treatment on CO2 adsorption performance of adsorbent (adsorption temperature is 75℃, CO2 concentration is 10%, adsorption time is 1h)
[0068]
[0069] Comparative Example 3. TEPA modified Mg 0.55 Al-CO3-AMOST adsorbent
[0070] 60TEPA-Mg 0.55 The preparation method of Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The difference in the preparation method of Al-CO3-AMOST material is that 0.75 g of tetraethylenepentamine (TEPA) is placed in 30 ml of methanol solution.
[0071] The adsorption-desorption cycle performance test method in Example 2 was used to determine the 60TEPA-Mg prepared in Comparative Example 3. 0.55 Al-CO3-AMOST adsorbent and implementation sample 60PEI-Mg 0.55 The recyclability of Al-CO3-AMOST adsorbent. The test results (Table 7) show that: 0.55 Although Al-CO3-AMOST showed a high adsorption capacity in the first cycle, its low melting and boiling points and thermal stability led to a rapid degradation of performance. The adsorption capacity in the last cycle was only 0.18 mmol g -1 The performance decay of the sample 60PEI-Mg 0.55 The Al-CO3-AMOST adsorbent exhibited excellent cyclic performance in 100 adsorption-desorption cycles, with a performance loss of only 6.7%. 0.55 Al-CO3-AMOST adsorbent has long-term stability, which is conducive to large-scale promotion and application.
[0072] Table 7 Effect of organic amine type (PEI, TEPA) on the performance of adsorbent CO2 absorption-desorption cycle
[0073]
[0074] Comparative Example 4. Grafted Amine-Mg 0.55 Al-CO3-AMOST adsorbent
[0075] Grafted TRI-Mg 0.55 The preparation method of Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The preparation method of Al-CO3-AMOST material is different in that 30 ml toluene solution containing 1.5 ml of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane is added dropwise at room temperature under nitrogen aeration to 0.5 g of dry Mg 0.55 Al-CO3 hydrotalcite powder was added to 30 ml toluene solution and stirred for 0.5 h. The temperature was quickly raised to 85 °C. The system was stirred and refluxed for 16 h. The solution was then centrifuged and washed at least twice in toluene, hexane, and methanol. Finally, the grafted TRI-Mg was obtained after drying in a vacuum oven at 60 °C overnight. 0.55 Al-CO3-AMOST adsorbent.
[0076] Grafted APTS-Mg 0.55 The preparation method of Al-CO3-AMOST adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The preparation method of Al-CO3-AMOST material is different in that 30 ml toluene solution containing 1.5 ml of 3-aminopropyltrimethoxysilane (APTS) is added dropwise at room temperature under nitrogen atmosphere to 0.5 g of dry Mg 0.55 Al-CO3 hydrotalcite powder was added to 30 ml toluene solution and stirred for 0.5 h. The temperature was quickly raised to 85 °C. The system was stirred and refluxed for 16 h. The solution was then centrifuged and washed at least twice in toluene, hexane and methanol. Finally, it was dried in a vacuum oven at 60 °C overnight to obtain the final grafted APTS-Mg 0.55 Al-CO3-AMOST adsorbent.
[0077] The adsorption capacity of the grafted TRI-Mg prepared in Comparative Example 4 was determined using the adsorption capacity test method in Example 1. 0.55 Al-CO3-AMOST adsorbent, grafted APTS-Mg 0.55 The CO2 adsorption performance of Al-CO3-AMOST adsorbent. The test results (Table 8) show that due to the grafted Amine-Mg 0.55The limited amine loading of Al-CO3-AMOST adsorbent and the consumption of a large number of organic amine sites during sample preparation resulted in poor CO2 adsorption performance. 0.55 Al-CO3-AMOST adsorbent and grafted TRI-Mg 0.55 The CO2 adsorption capacity of Al-CO3-AMOST adsorbent at 75℃ and 10% CO2 for 1h was 1.21mmol g -1 and 1.67mmol g -1 , only the sample 60PEI-Mg prepared by the present invention 0.55 The adsorption capacity of Al-CO3-AMOST adsorbent was 37.6% and 51.9%.
[0078] Table 8 Effect of preparation method (impregnation method, grafting method) on CO2 adsorption performance of adsorbent (adsorption temperature is 75°C, CO2 concentration is 10%, adsorption time is 1h)
[0079]
[0080] Comparative Example 5. Traditional silicon-based solid amine material
[0081] The preparation method of 60PEI-MCM-41 adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The difference in the preparation method of Al-CO3-AMOST material is that 0.5 g of dry MCM-41 powder is weighed and placed in polyethyleneimine solution and then vigorously stirred for 3 h at room temperature under nitrogen aeration.
[0082] The preparation method of 60PEI-SBA-15 adsorbent is similar to that of 60PEI-Mg in Example 1. 0.55 The difference in the preparation method of Al-CO3-AMOST material is that 0.5 g of dry SBA-15 powder is weighed and placed in polyethyleneimine solution and then vigorously stirred for 3 hours at room temperature and nitrogen aeration.
[0083] The adsorption capacity test method in Example 1 was used to measure the CO2 adsorption performance of the 60PEI-MCM-41 adsorbent and the 60PEI-SBA-15 adsorbent prepared in Comparative Example 5. Test results (Table 9 and Figure 5 ) showed that the carbon dioxide adsorption capacity of the conventional 60PEI-MCM-41 adsorbent and the 60PEI-SBA-15 adsorbent under 10% CO2 atmosphere for 1 hour was 2.21mmolg -1 and 3.09mmol g -1 Compared with traditional silicon-based solid amine materials, the 60PEI-Mg prepared in this invention 0.55Al-CO3-AMOST material has a better CO2 adsorption capacity, which is due to the fact that a large number of hydroxyl groups are exposed on the surface of LDH treated with organic solvents. These hydroxyl groups promote the dispersion of organic amines, resulting in an increase in the utilization rate of amines.
[0084] Table 9 Effect of carrier type on CO2 adsorption performance of adsorbent (adsorption temperature is 75℃, CO2 concentration is 10%, adsorption time is 1h)
[0085]
[0086] Based on the above experimental results, we get:
[0087] (1) For yPEI-A x BC-AMOST adsorbent, when A, B, and C are Mg 2+ 、Al 3+ 、CO3 2- When y=40-70wt% and x=0-3, it has a high CO2 adsorption capacity under 10% CO2 and low temperature (70-85℃). When y is 60wt% and x is 0.55, 3.32mmol g is obtained under the conditions of adsorption temperature of 75℃ and CO2 concentration of 10%. -1 The highest adsorption capacity was achieved and the highest stability was maintained during 100 adsorption-desorption cycle tests with a performance loss of only 6.7%, demonstrating that the polyethyleneimine-modified AMOST-type hydrotalcite-based adsorbent has excellent CO2 adsorption performance at low temperatures.
[0088] (2) Regarding the substrate of the adsorbent, the yPEI-Mg prepared using uncalcined LDH as the substrate in the present invention x The antioxidant performance of Al-CO3-AMOST adsorbent is significantly better than that of yPEI-Mg prepared based on calcined MMO. x Al-O MMO adsorbent, Mg 0.55 Comparative sample 60PEI-Mg prepared by calcining Al-CO3 LDH and then loading PEI 0.55 The oxidation resistance of Al-OMMO adsorbent is poor, and the performance shows obvious attenuation after oxidation treatment. The 60PEI-Mg prepared by LDH calcination temperature of 200℃, 300℃, 400℃ and 450℃ 0.55 Al-O MMO (200℃) adsorbent, 60PEI-Mg 0.55 Al-O MMO (300℃) adsorbent, 60PEI-Mg 0.55 Al-OMMO (400℃) adsorbent and 60PEI-Mg 0.55The Al-O MMO (450°C) adsorbent produced 8.5%, 12.4%, 13.8% and 15.5% performance losses during oxidation treatment (oxidation temperature of 120°C, oxygen concentration of 100%, oxidation time of 1h), respectively, while the 60PEI-Mg prepared by the present invention 0.55 No obvious performance loss was observed for the Al-CO3-AMOST adsorbent during the oxidation treatment under the same conditions, proving that the uncalcined AMOST LDH substrate used in the adsorbent preparation process of the present invention is superior.
[0089] (3) Regarding the preparation method of LDH, the AMOSTLDH-based adsorbent prepared by the organic solvent treatment method (AMOST) used in the present invention has a higher amine dispersion and better CO2 adsorption performance than the Water LDH-based adsorbent prepared by the traditional water washing method. When the adsorption temperature is 75°C and the CO2 concentration is 10%, the 60PEI-Mg prepared by the organic solvent treatment method (AMOST) 0.55 The adsorption capacity of Al-CO3-AMOST adsorbent (3.32mmol g -1 ) is much higher than the 60PEI-Mg prepared by the traditional water washing method 0.55 Al-CO3-Water LDH (0.42 mmol g -1 ) adsorbent.
[0090] (4) As for the type of organic amine, the present invention uses yPEI-A prepared from polyethyleneimine (PEI) x The CO2 adsorption-desorption cycle performance of BC-AMOST adsorbent is significantly better than that of yTEPA-A prepared with tetraethylenepentamine (TEPA). x BC-AMOST adsorbent, 60TEPA-Mg 0.55 The Al-CO3-AMOST adsorbent has a low melting point and thermal stability, which leads to a rapid performance decay in 100 cycles, with a performance loss rate of up to 94.9%. 0.55 The Al-CO3-AMOST adsorbent exhibited excellent recyclability in 100 adsorption-desorption cycles with a performance loss of only 6.7%, indicating that the polyethyleneimine (PEI) selected in the present invention is more suitable as an active site for low-temperature carbon capture.
[0091] (5) Regarding the modification method of the adsorbent, the organic amine-modified AMOST hydrotalcite-based adsorbent prepared by the impregnation method used in the present invention has better performance than the amine-modified AMOST hydrotalcite-based adsorbent prepared by the grafting method. 0.55The performance of Al-CO3-AMOST adsorbent is significantly higher than that of grafted APTS-Mg prepared by grafting method. 0.55 Al-CO3-AMOST adsorbent and grafted TRI-Mg 0.55 Al-CO3-AMOST adsorbent, when the adsorption temperature is 75°C and the CO2 concentration is 10%, for the 60PEI-Mg prepared by the present invention 0.55 Al-CO3-AMOST adsorbent, CO2 saturated adsorption capacity is 3.32mmol g -1 , while for grafted APTS-Mg 0.55 Al-CO3-AMOST adsorbent and grafted TRI-Mg 0.55 The saturated adsorption capacity of CO2 for Al-CO3-AMOST adsorbent was 1.21 mmol g -1 and 1.67mmol g -1 , proving that the preparation method of the adsorbent in the present invention is superior.
[0092] (6) Regarding the adsorbent carrier type, the 60PEI-Mg prepared by the present invention 0.55 Compared with traditional silicon-based solid amine materials 60PEI-MCM-41 adsorbent and 60PEI-SBA-15 adsorbent, Al-CO3-AMOST material has better CO2 adsorption performance, more dispersed organic amine sites, and higher amine utilization rate.
[0093] Based on the above experimental results, the inventors also conducted further experiments on the composition and molar fraction of each element in the adsorbent. The experimental results show that:
[0094] While ensuring high CO2 capture capacity at low temperatures, the chemical composition of the catalyst of the present invention can be expressed as yPEI-A x BC-AMOST, where y is the mass fraction of the organic amine in the material, y is 40-70wt%, and A can be Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ , Cu 2+ , Ca 2+ , Mn 2+ , Fe 2+ 、Zn 2+ At least one of the following, B can be A1 3+ Cr 3+ 、Co 3+ , Fe 3+ , Ga 3+ At least one of the following, C can be CO3 2- , NO3 - , SO42- , C2O4 2- , Cl - At least one of the following. Preferred adsorbents are as follows:
[0095] Preferably, y is 60wt%, and A is Mg 2+ , B is A1 3+ , C is CO3 2- , x is 0.55, the preferred chemical composition is 60PEI-Mg 0.55 Al-CO3-AMOST.
[0096] In addition, other parameters in the preparation method can also be adjusted. For example, the organic solvent is specifically at least one of anhydrous methanol, anhydrous ethanol and acetone; the pH value of the mixed solution in step (2) is controlled in the range of 8 to 12, more preferably in the range of 9.5 to 10.5; the vacuum drying temperature is 25°C to 120°C, and the vacuum degree is -0.1 to 0 MPa; the water bath temperature of the rotary evaporator is set to 25°C to 80°C, the rotation speed is 10 to 100 rpm, and the vacuum degree is -0.1 to 0 MPa.
[0097] The adsorbent prepared by the present invention can be used in a temperature range of 25 to 85° C. for CO2 capture, and a captured CO2 concentration range of 0.04% to 100%.
Claims
1. Application of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption, characterized in that: The composition system of the material is a hydrotalcite-like material treated with polyethyleneimine PEI-organic solvent, and its chemical composition is yPEI-A x BC-AMOST, y is the mass fraction of PEI in the material, A, B are the divalent and trivalent metal elements that make up the hydrotalcite-like layers, C is the anion between the layers, x is the molar ratio of the divalent and trivalent metal elements, y is 40-70wt%, x is 0.55-3, A x BC-AMOST is a hydrotalcite-like substance prepared by an organic solvent treatment method, wherein the organic solvent is specifically at least one of anhydrous methanol, anhydrous ethanol and acetone; the preparation method of the solid amine low-temperature carbon capture material comprises the following steps: (1) mixing two or more precursor substances containing A and B respectively to form a precursor solution; (2) adding the precursor solution to an alkaline solution to obtain a mixed solution, controlling the pH value of the mixed solution, and aging the mixed solution; (3) filtering and washing the aged mixed solution in deionized water and an organic solvent in turn, and then vacuum drying; The method comprises the following steps: (1) drying the mixture to obtain a hydrotalcite-like material containing A and B, wherein the specific process of the filtration and washing is as follows: under the condition of filtration, repeatedly washing the mixed solution with deionized water until the pH value of the filtrate is 7, and then washing the mixed solution with an organic solvent for 1 to 2 times when the filtrate is almost dried, and then drying the mixed solution to obtain a precipitate, placing the obtained precipitate in a container containing an organic solvent, and stirring the mixture at room temperature, and then filtration again, and repeatedly washing the filter cake with an organic solvent; (4) modifying the obtained hydrotalcite-like material with polyethyleneimine by a one-step impregnation method, and obtaining the yPEI-A after vacuum drying. x BC-AMOST solid amine low temperature carbon capture material.
2. The use of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption as claimed in claim 1, characterized in that: The chemical composition of the hydrotalcite-like material A x In BC, A is Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ , Cu 2+ , Ca 2+ , Mn 2+ , Fe 2+ At least one of the following, B is Al 3+ Cr 3+ 、Co 3+ , Fe 3+ , Ga 3+ At least one of the following, C is CO3 2- , NO3 - , SO4 2- , C2O4 2- , Cl - At least one of them.
3. The use of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption as claimed in claim 1, characterized in that: y is 60wt%, A, B, C are Mg 2+ 、Al 3+ 、CO3 2- , x is 0.55, chemical composition is 60PEI-Mg 0.55 Al-CO3-AMOST.
4. The use of a solid amine low-temperature carbon capture material according to claim 1 in low-temperature CO2 adsorption, characterized in that: In step (2), the pH value of the mixed solution is controlled within the range of 8 to 12, the aging temperature is 25 to 80° C., and the aging time is greater than 2 hours.
5. The use of a solid amine low-temperature carbon capture material according to claim 4 in low-temperature CO2 adsorption, characterized in that: The pH value of the mixed solution in step (2) is controlled within the range of 9.5 to 10.
5.
6. The use of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption as claimed in claim 1, characterized in that: The vacuum drying temperature in step (3) is 25 to 120° C., and the vacuum degree is -0.1 to 0 MPa.
7. The use of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption as claimed in claim 1, characterized in that: The one-step impregnation process in step (4) is specifically as follows: adding a certain mass of polyethyleneimine to an organic solvent and stirring it thoroughly at room temperature; weighing a certain mass of hydrotalcite-like material and placing it in the polyethyleneimine solution and continuing to stir vigorously at room temperature; using a rotary evaporator to remove the organic solvent in the mixed solution, and obtaining the yPEI-A after vacuum drying. x BC-AMOST solid amine low temperature carbon capture material.
8. The use of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption as claimed in claim 7, characterized in that: The stirring process in step (4) is carried out under air-tight conditions, with a rotation speed of 10 to 100 rpm, a vacuum drying oven temperature of 25 to 120° C., and a vacuum degree of -0.1 to 0 MPa.
9. The use of a solid amine low-temperature carbon capture material in low-temperature CO2 adsorption as claimed in claim 8, characterized in that: The isolated air is nitrogen.
Citation Information
Patent Citations
Compound type intermediate-temperature carbon dioxide adsorbent and preparation method thereof
CN105797678A
Amino modified hydrotalcite adsorbent and preparation method thereof
CN110420617A
